Numerical study on flow past an oscillating plate with variable temperature and uniform mass diffusion under chemical reaction - Vijayalakshmi, A.R.; Selvajayanthi, Murugan (Zielona Góra: Uniwersytet Zielonogórski)
An numerical study on an unsteady flow past an oscillating semi-infinite vertical plate with variable temperature and uniform mass diffusion under the influence of a first order chemical reaction has been carried out. The dimensionless governing equations are solved by an unconditionally stable and fast converging implicit finite difference scheme. The effects of velocity and temperature for different physical parameters such as the chemical reaction parameter, thermal Grashof number, mass Grashof number and time are analysed. It is observed that due to the presence of first order chemical reaction, the velocity increases during a generative reaction and decreases in a destructive reaction.
Keywords: chemical reaction; oscillating vertical plate; heat transfer; mass diffusion